Mapping apologetics: comparing contemporary approaches - Morley, Brian K. (IVP Academic, an imprint of Intervarsity Press, 2015)
"In this comprehensive survey, Brian Morley provides an overview of Christian apologetic approaches and how they differ. He explores the historical and philosophical underpinnings of key figures and major schools of thought, from the presuppositionalism of Cornelius Van Til to the evidentialism of Gary Habermas. Moving beyond theory, Morley also covers apologetic application, demonstrating how each view works out in practical terms. This guide covers the complexities of apologetics in a way that is accessible to the nonspecialist. Even-handed and respectful of each apologist and their contribution, this book provides the reader with a formidable array of defenses for the faith." -- Back Cover